The Effect Of Need For Uniqueness And Bandwagon Effect On Purchase Intentions Through The Hedonic Function Of Attitude As An Intervening Variable In Purchasing An Iphone 15 Promax Smartphone(Study On Generation Z Pontianak) - Rindi Astuti; Heriyadi Heriyadi; Juniwati Juniwati; Ramadania Ramadania (UNIVED Press, 2025)
This study aims to analyse the effect of Need for Uniqueness and Bandwagon Effect on Purchase Intentions with Hedonic Function of Attitude as an intervening variable in the purchase of iPhone 15 Pro Max. The sample was taken using purposive sampling, with a total of 150 respondents. The data analysis method uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) with WarpPls 8.0. The results showed that Need for Uniqueness and Bandwagon Effect have a significant effect on Purchase Intention through the mediation of Hedonic Function of Attitude. These findings emphasise the importance of marketing strategies that focus on product uniqueness and consumers' hedonic experiences.